Octogenarians with chronic kidney disease in the nephrology clinic: Progressors vs. non-progressors - Frías, Aida; Vargas, Francisco; Sandino, Justo; Berzal, Raquel; Rivero, Marta; Cordero, Lucía; Cavero, Teresa; Segura, Julián; García, Florencio; Hernández, Eduardo; Gutiérrez, Eduardo; Auñón, Pilar; et al. (Frontiers in Nephrology, 2023)
Background: The current definition of chronic kidney disease applied to patients over the age of 80 has increased the number of referrals to Nephrology. However not all of these patients may benefit from its assessment. This study aims to analyze the evolution of ≥80 years old patients referred to Nephrology. Methods: Single-center study including patients ≥80 years old with eGFR <60 mL/min/1,73m2 who were referred to Nephrology consultation for the first time. Clinical and analytical parameters were collected retrospectively 12 months before the visit, and prospectively at baseline, and 12 and 24 months after the initial visit. We divided patients into two groups based on annual eGFR loss: progressors (>5 mL/min/1.73m2) and non-progressors (≤5 mL/min/1,73m2). Results: A total of 318 patients were included, mean age was 84,9 ± 4 (80-97) years. Baseline serum creatinine was 1,65 ± 0,62 mg/dL, eGRF 35 (28-42) mL/min/1,73, and albumin/creatinine ratio 36 (7-229) mg/g. 55,7% of the patients met the definition of progressor at baseline (initial-progressors), 26,3% were progressors after a 12-month follow-up and 13,4% after 24 months. 21,2% and 11,4% of initial-progressors met this definition at 12 and 24 month follow up. The main risk factor for progression was albuminuria. No relationship was found between the nephrologist intervention and the evolution of renal function among initial non-progressors. Conclusions: Elderly patients who have stable renal function at the time of referral will continue to have stable renal function over the subsequent 24 months and thus may not need to be referred to a nephrologist.